Long-term evaluation of home-based pulmonary rehabilitation in patients with fibrotic idiopathic interstitial pneumonias - Wallaert, Benoit (ERJ Open Res, 2019)
BACKGROUND: Few studies have examined the benefits of pulmonary rehabilitation in patients with fibrotic idiopathic pulmonary pneumonia (f-IIP). Here, we report the results of an observational study in routine clinical practice of home-based pulmonary rehabilitation for f-IIP patients. METHODS: A total of 112 consecutive patients (61 with idiopathic pulmonary fibrosis and 51 with fibrotic nonspecific interstitial pneumonitis) were enrolled, of whom 65 had mild-to-moderate disease (forced vital capacity (FVC) ≥50% predicted and diffusing capacity of the lung for carbon monoxide (D(LCO)) ≥30% predicted) and 47 had severe disease (FVC <50% predicted and/or D(LCO) <30% predicted). The 2-month pulmonary rehabilitation programme consisted of a once-weekly visit with retraining, therapeutic education and psychosocial support. Patients were provided with an individualised action plan and were followed-up bimonthly for 12 months. Exercise tolerance (6-min stepper test (6MST)), mood (Hospital Anxiety and Depression Scale (HADS)) and quality of life (QoL) (Visual Simplified Respiratory Questionnaire (VSRQ)) were assessed before (T(0)), immediately after (T(2)), 6 months after (T(8)) and 12 months after (T(14)) the end of the pulmonary rehabilitation programme. RESULTS: 6MST strokes, HADS Anxiety score and VSRQ score were each significantly improved at T(2) (n=101), T(8) (n=76) and T(14) (n=62) compared with T(0) values. The improvements in outcomes were not influenced by disease severity or subtype. Patients who completed the study had significantly better baseline FVC and D(LCO) values than those who did not. CONCLUSIONS: Home-based pulmonary rehabilitation provides long-term benefits in exercise tolerance, anxiety and QoL for patients with f-IIP. Pulmonary rehabilitation should be prescribed systematically as part of the therapeutic arsenal for these patients.